Penerapan Model Pembelajaran Perubahan Konseptual Terhadap Pemahaman Siswa Pada Materi Larutan Penyangga - Sindi Hana Simbar; Tiene Turangan; Sofia Krisen (Oxygenius Journal Of Chemistry Education, 2021)
Of research on application of Case Based Learning Model on Material of Buffer Solution to Student Result of Class XI IPA of SMA Negeri 1 Kawangkoan. The purpose of this research is to know the difference of student learning resultusing conventional case-based learning model on buffer material. The research method used is experimental research method with the research design used is Posttest Only Control Group Design. Data collection technique is posttest. The research population is all students of SMA Negeri 1 Kawangkoan, while the samples taken are two randomly selected classes, that is class XI IPA 4 as experiment class with 25 students and class XI IPA 5 as control class with 25 students. Based on the results of research analyzed by t-test at the real level (α) = 0.05 obtained data that tcount = 2.494 and ttable = 1.677 according to the study criteria, if tcount> ttable then reject H0, so it can be concluded that there are differences in results student learning is taught by case-based learning model with student learning outcomes using conventionallearning method.